2022
DOI: 10.3390/jrfm15120577
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Governance in Investment Efficiency and Financial Information Disclosure Risk in Companies Listed on the Tehran Stock Exchange

Abstract: This study’s primary purpose is to investigate corporate governance’s role in investment efficiency and financial information disclosure risk in companies listed on the Tehran Stock Exchange. A multivariate linear regression model based on the panel data model was used to test the research hypotheses. The results of the survey of 140 companies listed on the Tehran Stock Exchange from2015 to 2021 indicate that investment efficiency has increased by increasing the quality of corporate governance. In addition, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The results showed a strong correlation between corporate governance and firm performance, indicating that effective corporate governance can lead to sustainable firm performance over the long term. Kashani & Mousavi Shiri (2022) explored the role of corporate governance in investment efficiency and financial information disclosure risk in companies listed on the Tehran stock exchange. The study found that improving the quality of corporate governance can significantly reduce the risk of financial information disclosure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a strong correlation between corporate governance and firm performance, indicating that effective corporate governance can lead to sustainable firm performance over the long term. Kashani & Mousavi Shiri (2022) explored the role of corporate governance in investment efficiency and financial information disclosure risk in companies listed on the Tehran stock exchange. The study found that improving the quality of corporate governance can significantly reduce the risk of financial information disclosure.…”
Section: Resultsmentioning
confidence: 99%
“…Effective corporate governance is enormously dependent on the boards of directors, as they play a crucial role in overseeing the risk management practices of a company (Kashani & Mousavi Shiri, 2022). Therefore, these authors highlight that it is imperative to establish a well-structured board with independent directors and maintain transparent communication with the leaders.…”
Section: Boards Of Directorsmentioning
confidence: 99%
“…The size of a corporation has little influence on the accuracy of its financial records, regardless of any assertions suggested otherwise. While not all big firms have extensive experience in preparing financial statements, small enterprises often have more proficiency in ensuring the accuracy of their financial records (Kashani & Mousavi Shiri, 2022). Therefore, financial statement integrity is not guaranteed by a tiny company's size, as shown by a modest market capitalization, book value, and earnings.…”
Section: The Influence Of Independent Commissioners On the Integrity ...mentioning
confidence: 99%
“…The Tehran Stock Exchange has seen increased fraudulent reporting through transactions with related parties, highlighting the need for effective corporate governance (Pakdelan et al, 2022). Additionally, the quality of corporate governance has been found to impact investment efficiency and the risk of financial information disclosure (Kashani & Mousavi Shiri, 2022). Furthermore, the optimal selection of stock portfolios using multi-criteria decision-making methods has been studied, providing insights into maximizing returns and minimizing risk (Jing et al, 2023).…”
Section: Introductionmentioning
confidence: 99%